Displaying epistemic stance through same-turn self-repair in Chinese civil courtroom interaction - Xu, Jun; Ge, Lei (Frontiers in Psychology, 2023)
Repair, or conversational repair, frequently appears in court proceedings as a vital mechanism sustaining effective communication. Our study presents a conversational analysis of the choices of different operations in the same-turn self-repair and shows how judges, plaintiffs, defendants, and their lawyers deploy those operations based on a model of epistemic stance. The data were drawn from the top five most-viewed videos of Changsha civil courtrooms from March to May, 2019, totaling more than 50,000 words. In the courtroom interaction, replacing and inserting are the most frequently used operations for all participants. In the courtroom cross-examinations, interlocutors use discrepant same-turn self-repair operations to achieve single or multiple communicative goals, such as improving precision, increasing credibility, highlighting their points, skirting questions, and confirming information. Additionally, when the epistemic stance of the trouble source is [K+], speakers employ most same-turn self-repair operations to keep their [K+] epistemic stance by improving precision and increasing credibility of their utterances or use reformatting or inserting to downgrade epistemic stance to [K−] by decreasing the certainty of their utterances. These findings shed light on the understanding of same-turn self-repairs in the institutional interaction, particularly in Chinese civil courtroom interaction.